Todani Type II Congenital Bile Duct Cyst: European Multicenter Study of the French Surgical Association and Literature Review. Issue 1 (July 2015) - Ouaïssi, Mehdi; Kianmanesh, Reza; Belghiti, Jacques; Ragot, Emilia; Mentha, Gilles; Adham, Mustapha; Troisi, Roberto Ivan; Pruvot, François-René; Dugué, Laurent; Paye, François; Ayav, Ahmet; Nuzzo, Gennaro; et al.
Abstract : Objective: The purpose of the study was to analyze clinical presentation, surgical management, and long-term outcome of patients suffering from biliary diverticulum, namely Todani type II congenital bile duct cyst (BDC). Background: The disease incidence ranges between 0.8% and 5% of all reported BDC cases with a lack of information about clinical presentation, management, and outcome. Methods: A multicenter European retrospective study was conducted by the French Surgical Association. The patients' medical records were included in a Web site database. Diagnostic imaging studies, operative and pathology reports underwent central revision. Results: Among 350 patients with congenital BDC, 19 type II were identified (5.4%), 17 in adults (89.5%) and 2 in children. The biliary diverticulum was located at the upper, middle, and lower part of the extrahepatic biliary tree in 11, 4, and 4 patients (58%, 21%, and 21%, respectively). Complicated presentation occurred in 6 patients (31.6%), including one case of synchronous carcinoma. Surgical techniques included diverticulum excision in all patients. Associated resection of the extrahepatic biliary tree was required in 11 cases (58%) and could be predicted by the presence of complicated clinical presentation. There was no mortality. Long-term outcome was excellent in 89.5% of patients (median follow-uptime: 52 months). Conclusions: According to the present largest Western series of Todani type II BDC, the type of clinical presentation rather than BDC location, was able to guide the extent of biliary resection. Excellent long-term outcome can be achieved in expert centers. Abstract : Congenital biliary diverticulum, namely, Todani type II bile duct cyst, is a rare disease. Surgical resection is the treatment of choice, requiring associated bile duct resection in 58% of the patients with excellent long-term outcome. Synchronous cancer may be associated.